Harnessing unconventional monomers to tailor lignin structures for lignocellulosic biomass valorization - Yunjun Zhao; Muhammad Abid; Xinxin Xie; Yuelin Fu; Yuxiang Huang; Zhuoying Cai; Huana Lin (Forestry Research, 2024)
Lignin is an integral component in the plant secondary cell wall that imparts structural rigidity and integrity to plant tissues, contributes to the formation of the plant vascular system, and provides stress resilience. However, the heterogeneity and recalcitrance of lignin greatly impede the effective utilization of lignocellulosic biomass which represents the most abundant and valuable biogenic source for green and sustainable bioproducts. A customized lignin structure has the potential to alter lignin physicochemical properties and improve biomass utilization. Recently, researchers have reported that lignin polymerization can employ monomers beyond the traditional three monomers. The incorporation of these unconventional monomers can alter the physicochemical properties of lignin polymer by imparting lignin with a whole new structure. Here, we review the plant engineering efforts to alter lignin content, composition, and structure by harnessing non-conventional monomers. Rational manipulation of lignin structure with these unconventional lignin monomers may provide new strategies for minimizing the impacts of engineered lignin on plant growth and development meanwhile improving the utilization efficiency of lignocellulosic biomass.